Current status of PSMA PET imaging in prostate cancer. (27th August 2020) - Ho, Chi Lai; Wu, Kwan Kit; Chen, Sirong
Abstract: The past decade has witnessed the rising popularity and acceptance of molecular definitions on disease management. Prostate‐specific membrane antigen (PSMA), in light of its molecular nature and cytokinetic properties, has rapidly become the target for development of a variety of functional tracers for PET/CT evaluation of prostate cancer. The most commonly used PSMA‐binding analog is 68 Ga‐labeled PSMA‐11, which is now widely applied in both research and clinical settings. Literature data in the recent years have been enriched by a number of meta‐analyses and systemic reviews on the evolving role of PSMA PET in primary diagnosis, staging, detection of biochemical recurrence after primary cancer treatment, identification, and significance of oligometastasis, as well as in restaging and treatment monitoring. Being a highly sensitive and reasonably specific molecular tracer, PSMA‐binding analogs have a high potential to possess the majority of imaging characteristics required for a variety of management decisions in prostate malignancy.